Influence of E-Liquid Humectants, Nicotine, and Flavorings on Aerosol Particle Size Distribution and Implications for Modeling Respiratory Deposition - Stefaniak, Aleksandr B.; Ranpara, Anand C.; Virji, Mohammed Abbas; LeBouf, Ryan F. (Frontiers in public health, 2022)
Electronic cigarette, or vaping, products are used to heat an e-liquid to form an aerosol (liquid droplets suspended in gas) that the user inhales; a portion of this aerosol deposits in their respiratory tract and the remainder is exhaled, thereby potentially creating opportunity for secondhand exposure to bystanders (e.g., in homes, automobiles, and workplaces). Particle size, a critical factor in respiratory deposition (and therefore potential for secondhand exposure), could be influenced by e-liquid composition. Hence, the purposes of this study were to (1) test the influence of laboratory-prepared e-liquid composition [ratio of propylene glycol (PG) to vegetable glycerin (VG) humectants, nicotine, and flavorings] on particle size distribution and (2) model respiratory dosimetry. All e-liquids were aerosolized using a second-generation reference e-cigarette. We measured particle size distribution based on mass using a low-flow cascade impactor (LFCI) and size distribution based on number using real-time mobility sizers. Mass median aerodynamic diameters (MMADs) of aerosol from e-liquids that contained only humectants were significantly larger compared with e-liquids that contained flavorings or nicotine ( p = 0.005). Humectant ratio significantly influenced MMADs; all aerosols from e-liquids prepared with 70:30 PG:VG were significantly larger compared with e-liquids prepared with 30:70 PG:VG ( p = 0.017). In contrast to the LFCI approach, the high dilution and sampling flow rate of a fast mobility particle sizer strongly influenced particle size measurements (i.e., all calculated MMAD values were < 75 nm). Dosimetry modeling using LFCI data indicated that a portion of inhaled particles will deposit throughout the respiratory tract, though statistical differences in aerosol MMADs among e-liquid formulations did not translate into large differences in deposition estimates. A portion of inhaled aerosol will be exhaled and could be a source for secondhand exposure. Use of laboratory-prepared e-liquids and a reference e-cigarette to standardize aerosol generation and a LFCI to measure particle size distribution without dilution represents an improved method to characterize physical properties of volatile aerosol particles and permitted determination of MMAD values more representative of e-cigarette aerosol in situ , which in turn, can help to improve dose modeling for users and bystanders.